2022
DOI: 10.1007/s10584-022-03318-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of serious gaming on risk perceptions of climate tipping points

Abstract: A growing body of research indicates that effective science-policy interactions demand novel approaches, especially in policy domains with long time horizons like climate change. Serious games offer promising opportunities in this regard, but empirical research on game effects and games’ effectiveness in supporting science-policy engagement remains limited. We investigated the effects of a role-playing simulation game on risk perceptions associated with climate tipping points among a knowledgeable and engaged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…The explorative nature of this study allowed for the pre-service teachers to come with their own thoughts about how the game conveys climate change, including its uncertainties. Though other approaches have documented learning effects on climate change uncertainty particularly for simulation games, for example on possible tipping points (van Beek et al, 2022) and the differences between uncertainty due to natural fluctuations and human-induced climate change in water management (van Pelt et al, 2015), this study has found that pre-service teachers addressed a wide range of topics related to climate change uncertainty in response to questions regarding board games. Perhaps coloured by the Norwegian national elections being held some days prior to the game sessions, politics was a recurrent theme in the pre-service teachers’ discussions.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The explorative nature of this study allowed for the pre-service teachers to come with their own thoughts about how the game conveys climate change, including its uncertainties. Though other approaches have documented learning effects on climate change uncertainty particularly for simulation games, for example on possible tipping points (van Beek et al, 2022) and the differences between uncertainty due to natural fluctuations and human-induced climate change in water management (van Pelt et al, 2015), this study has found that pre-service teachers addressed a wide range of topics related to climate change uncertainty in response to questions regarding board games. Perhaps coloured by the Norwegian national elections being held some days prior to the game sessions, politics was a recurrent theme in the pre-service teachers’ discussions.…”
Section: Discussionmentioning
confidence: 82%
“…As such, the player is motivated to play the game again and uncover other scenarios (Schroth et al, 2014), exploring uncertainty regarding climate change measures and the future. Games, including board games and digital games, may cover a range of different climate change-related uncertainties (e.g., Caracciolo, 2022; van Beek et al, 2022; van Pelt et al, 2015; van Schaik, 2023).
Figure 1.Climate change games and their representations and interpretations in the context of climate change as an issue and discourse.
…”
Section: Introductionmentioning
confidence: 99%
“…Social media has shown promise for increasing the awareness of climate change in general (Mavrodieva et al, 2019), and with no relationship between the use of social media and awareness of climate tipping points found here, its potential appears so far untapped. Other possibilities include serious gaming, which has been shown to reduce the psychological distance of climate tipping points and provide effective science-policy engagement tools (Van Beek et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These nonlinear changes are closely associated with the nonlinear changes in climatic factors or human activities. Previous studies have reported that the climate [28,73,74], human impacts on the Earth's systems [75,76], and even the relationship between vegetation greenness and rainfall [77] have all experienced frequently nonlinear changes in the past. However, because of the differences in study areas, study periods, research objects (satellite-based vegetation indicators, thematic LCC, or comprehensive indicators derived from general LCCs), and the method of nonlinear diagnosis (statistical analysis of vegetation trajectories or observation of annual consequence of general LCCs), the derived results are not comparable.…”
Section: Nonlinear Evolutionary Paths Of Global Arid Ecosystemsmentioning
confidence: 99%